2020
DOI: 10.1016/j.jtho.2019.12.110
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Eighth Edition Clinical T Categorization System for Clinical Stage IA, Resected Lung Adenocarcinomas: Prognostic Implications of the Ground-Glass Opacity Component

Abstract: Introduction: There is controversy regarding the clinical T (cT) category of lung adenocarcinomas that manifest as part-solid nodules (PSNs). We aimed to validate the cT category and to evaluate the independent prognostic role of the nodule type (i.e., part-solid versus solid). Methods: We retrospectively evaluated the prognostic value of clinico-radiologic factors regarding the overall survival of patients with clinical stage IA lung adenocarcinomas that were resected between 2008 and 2014. cT Category, nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
3
16
1
Order By: Relevance
“…For instance, although smoking is considered to be a main risk factor of lung cancer, the majority of smokers will not develop lung cancer in their lifetime (37) and some never-smokers might also develop lung cancer. Moreover, the percentage of never smokers in lung cancer patients is about 10% to 20% in western countries (38), but it is as high as 50% to 63% in east-Asian population (39)(40)(41). Mechanically, gene nutation might be a significant factor and some genetic variations might contribute to the carcinogenesis of non-small cell lung cancer regardless of smoking history.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…For instance, although smoking is considered to be a main risk factor of lung cancer, the majority of smokers will not develop lung cancer in their lifetime (37) and some never-smokers might also develop lung cancer. Moreover, the percentage of never smokers in lung cancer patients is about 10% to 20% in western countries (38), but it is as high as 50% to 63% in east-Asian population (39)(40)(41). Mechanically, gene nutation might be a significant factor and some genetic variations might contribute to the carcinogenesis of non-small cell lung cancer regardless of smoking history.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…It most often affects the skin, but there are also reports of other organs and systems, such as the lung, gastrointestinal tract, muscle, and central nervous system being affected. 1 It is reported that several chemotherapy and target therapy drugs can cause RRR. With the emergence and frequent use of immune checkpoint inhibitors (ICIs), reports of immunotherapy-induced RRR began to appear in the literature.…”
Section: Concomitant Radiation Recall Dermatitis and Radiation Recall Pneumonitis Induced By Pembrolizumabmentioning
confidence: 99%
“…The incidence of RRR triggered by chemotherapeutic drugs is 8.8%. 1 The incidence of RRP caused by targeted therapy is 4.4%. 3 The incidence of RRR induced by ICI is unknown owing to the rarity of the disease.…”
Section: Concomitant Radiation Recall Dermatitis and Radiation Recall Pneumonitis Induced By Pembrolizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsolid nodules often represent premalignancy or early spectrum lung adenocarcinoma, including premalignant lesions of atypical adenomatous hyperplasia and adenocarcinoma in situ, minimally invasive adenocarcinoma, or lepidic predominant invasive adenocarcinoma (Travis et al, 2016). Studies suggest that subsolid nodules that are predominantly ground glass portend a significantly better prognosis compared to lung adenocarcinomas (ADC) that present as part-solid or solid lesions (Aokage et al, 2018;Berry et al, 2018;Hattori et al, 2017;Kim et al, 2020). Some subsolid nodules remain stable for many years while others may progress to invasive disease.…”
Section: Introductionmentioning
confidence: 99%